2005
DOI: 10.1089/apc.2005.19.449
|View full text |Cite
|
Sign up to set email alerts
|

HIV Health Care Access Issues for Women Living with HIV, Mental Illness, and Substance Abuse

Abstract: Nurses at the Well-Being Institute, a community-based nursing outreach clinic in Detroit, Michigan, located 75 women living with HIV, mental illness, and substance abuse who were lost to follow-up at their HIV medical clinic as part of a nursing research study. Women who had been scheduled for an appointment in the last 4 months but who had missed that appointment were considered "lost to follow-up" in the HIV clinic. The purpose of the research was to study factors related to health care access in women not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…20 Although there is scant literature on the association of substance abuse with primary care or gynecological appointment adherence, several studies examining the HIV-infected population in general have linked such factors as substance abuse to HIV medication nonadherence. [28][29][30][31] One study of 150 HIV-infected people found that drug use was associated with a 4-fold greater risk of medication adherence failure. 32 Unfortunately substance use and abuse in women is closely linked to HIV: the CDC reported that 1 in 5 new HIV diagnoses in women were related to injection drug use in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although there is scant literature on the association of substance abuse with primary care or gynecological appointment adherence, several studies examining the HIV-infected population in general have linked such factors as substance abuse to HIV medication nonadherence. [28][29][30][31] One study of 150 HIV-infected people found that drug use was associated with a 4-fold greater risk of medication adherence failure. 32 Unfortunately substance use and abuse in women is closely linked to HIV: the CDC reported that 1 in 5 new HIV diagnoses in women were related to injection drug use in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Adapting levels of service to client characteristics is the basic premise of this study. This approach is suggested by data from an earlier WBI study (Andersen et al, 2005) that reported that current heroin use in the past 30 days and current mental health symptoms can differentiate intensity of intervention required to effect the desired outcome of retention in HIV primary medical care. The WBI results are further supported in the literature (Knowlton et al, 2001;Magnus et al, 2001;Stoskopf et al, 2001).…”
Section: Ancillary Service Level Assignmentmentioning
confidence: 99%
“…The Personalized Nursing LIGHT Model is described in many publications (Andersen & Hockman, 1997;Andersen & Smereck, 1989, 1992; Andersen, Smereck, & Braunstein, 1993;Andersen et al, 1999;Andersen et al, 2005). The LIGHT Model posits that positive changes among hard-toreach populations having histories of nonresponsiveness to more traditional treatment methods may be achieved indirectly through a direct intervention on the perceived well-being of the individual.…”
Section: Transportation Plus Personalized Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Depression and other mood disorders, anxiety disorders, and posttraumatic stress disorder (PTSD) have been identified as the most prevalent diagnoses among HIV-infected individuals. Mental illness among individuals with HIV has been associated with negative outcomes including decreased quality of life, 4,[6][7][8] AIDS-related morbidity and mortality, 9,10 delayed entry into medical care, 5,11,12 poorer medication adherence, 4,8,[13][14][15] risky sexual and drug use behaviors 12,16 and substantial costs including productivity loss and health care expenditures. 10,17,18 Mental health treatment, including mental health counseling and psychopharmacologic treatment, has been associated with improvements in mental health functioning [19][20][21][22][23][24][25][26] as well as greater HIV-related medication use and adherence 10,19,[27][28][29][30][31] and higher CD4 counts.…”
Section: Introductionmentioning
confidence: 99%